Psychopharmacological Support Significance on Attention Deficit Hyperactivity Disorder - Haq, Farah (International Journal of Psychology, 2025)
Purpose: This paper explores Attention-Deficit Hyperactivity Disorder (ADHD), focusing on its treatment approaches, based on its multifaceted etiology, and symptomatology. Methodology: Literature review of current research on the topic was selected as the methodology for the paper. Drawing from an extensive current and peer reviewed articles, the study examines genetic, neurological, environmental, and sociocultural influences on ADHD. Psychopharmacological treatments, particularly stimulants like Methylphenidate, are identified as highly effective, along with considerations for potential side effects and misuse. Alternative therapies such as Acetyl-L-Carnitine, Cognitive Behavioral Therapy (CBT), and Sensory Integration have also been examined through the review process. Findings: With the help of an exhaustive review process, the paper initiates a discussion for the complementary and possibly influential elements for creating a best support system for ADHD. Findings also lead to research gaps due to the limited data on working memory dysfunction, maternal stress impacts, and neurofeedback interventions, alongside inadequate exploration of diet-based treatments. Key findings emphasize the importance of combining pharmacological and behavioral therapies to address ADHD's cognitive, emotional, and behavioral dimensions. While genetic predispositions play a significant role, sociocultural contexts and environmental factors critically influence symptom expression and management. Unique Contribution to Theory, Practice and Policy: The findings of this review underscore several important recommendations. There is a clear need for culturally adaptive and holistic treatment strategies to address ADHD effectively. Future research should prioritize the expansion of evidence-based approaches, investigate neurodevelopmental connections more deeply, and enhance the accessibility of alternative and integrative treatment options.